Rehabilitation of Annular Pulley Injuries of the Fingers in Climbers: A Clinical Commentary - Ehiogu, Uzo Dimma; Schöffl, Volker; Jones, Gareth (Current Sports Medicine Reports, 2023)
The annular pulley ligaments of the fingers are one of the most injured anatomical structures in those who participate in climbing. Despite this, there is a paucity of guidance clearly describing the rehabilitation and physical preparation parameters to return to sport following such injuries. The foundation of effective rehabilitation is the judicious application of progressive loading to increase the morphological and material properties of the damaged tissues. We maintain the optimal management of the climbing athlete after a traumatic annular flexor pulley system rupture should be grounded in the principles of strength and conditioning.
CRIS-Team Scopus Importer:2023-11-03